Phaneroptera Serville and Anormalous gen. nov. (Orthoptera: Tettigoniidae: Phaneropterinae) from China, with description of two new species - Liu, Chun-Xiang (Zootaxa, 2011)
A list of and key to Phaneroptera from China is provided. One new species with comparatively short hind wings, Phaneroptera brevicauda sp. nov. is described. And a new small-sized genus and new species Anormalous zhangi sp. gen. & nov. is also described here. The new genus most resembles the genera in the tribe Ducetiini in shape of lateral lobe of pronotum, structure of the tympana, shape of fore tibiae, and male subgenital plate without styli, but differs by the special tegminal structure. Both new species are distributed in southwestern China. Necessary illustrations are provided.